Book review: Earth materials. Introduction to mineralogy and petrology (Second edition), by Cornelis Klein and Anthony R. Philpotts, 2017. Cambridge University Press, Cambridge, UK. 616 pages. Paperback: price £44.99 ISBN: 9781316608852. - Duczmal-Czernikiewicz, Agata (Geologos, 2021)
Book review: Earth materials. Introduction to mineralogy and petrology (Second edition), by Cornelis Klein and Anthony R. Philpotts, 2017. Cambridge University Press, Cambridge, UK. 616 pages. Paperback: price £44.99 ISBN: 9781316608852.